Achieving Histologic Normalization in Ulcerative Colitis Is Associated With a Reduced Risk of Subsequent Dysplasia. Issue 4 (30th April 2022) - Shaffer, Seth R; Erondu, Amarachi I; Traboulsi, Cindy; Rai, Victoria; Krugliak Cleveland, Noa; Israel, Amanda; Christensen, Britt; Rubin, David T
Abstract: Background: Complete histologic normalization is associated with improved clinical outcomes in ulcerative colitis (UC). However, it is currently unknown what effect achieving histologic normalization has on the development of dysplasia. Methods: We performed a retrospective analysis of 495 patients with a confirmed diagnosis of UC from a tertiary center. Patients were categorized according to the best histologic assessment they had during their disease course: histologic normalization, histologic quiescence, or persistent histologic activity. We assessed dysplasia rates in these patient groups after achieving histologic normalization or histologic quiescence, or 8 years after UC diagnosis in those with persistent histologic activity. Kaplan-Meier graphs and Cox regression analyses were performed to estimate this effect. Results: The incidence rate of dysplasia development after achieving histologic normalization was statistically significantly less when compared with the incidence rate after achieving histologic quiescence ( P = 0.001) and in those with persistent histologic activity 8 years after UC diagnosis ( P = 0.033). In multivariate analysis, at any point throughout UC duration, dysplasia development was statistically lower in those with histologic normalization (adjusted hazard ratio [aHR], 0.32; 95% confidence interval [CI], 0.13-0.81) but not in those with histologic quiescence (aHR, 0.52; 95% CI, 0.25-1.10), compared with those with persistent histologic inflammation. When assessing the time after achieving histologic normalization, histologic quiescence, or 8 years post UC diagnosis in those with persistent histologic activity, we found that patients with histologic normalization had a subsequent decreased risk of developing dysplasia (aHR, 0.09; 95% CI, 0.01-0.72), compared with patients without normalization. Conclusions: Histologic normalization is associated with a decreased risk in patients with UC of developing subsequent dysplasia, compared with patients without histologic normalization. These findings have implications for surveillance intervals.